PERPADUAN GAYA ARSITEKTUR TIMUR TENGAH, EROPA DAN LOKAL PADA BANGUNAN MASJID AL- AZHOM TANGERANG - Ade Syoufa; Mega Aryani Amalia (Jurnal Teknik dan Science, 2023)
Mosques in Indonesia have several attractive architectural designs thanks to the combination of styles, one of which is the Al-Azhom Grand Mosque in Tangerang City. This mosque is an icon of Tangerang City which has an unusual dome and refers to the style of the XVIII and XIX centuries. Therefore, this study aims to find out which architectural style blends exist in the Al-Azhom Grand Mosque in Tangerang City. The method used in this study is a qualitative method, with the analytical method used is a descriptive method, namely describing building objects in the Al-Azhom Grand Mosque area from history and analyzing field data objects with literature studies and adjusting objects into mosque architectural styles. The results show that the Al-Azhom Grand Mosque Tangerang is influenced by architectural styles originating from Middle Eastern culture, European culture, and local culture.